Tsc2 shapes olfactory bulb granule cell molecular and morphological characteristics - Riley, Victoria A.; Holmberg, Jennie C.; Sokolov, Aidan M.; Feliciano, David M. (Frontiers in Molecular Neuroscience, 2022)
Tuberous Sclerosis Complex (TSC) is a neurodevelopmental disorder caused by mutations that inactivate TSC1 or TSC2. Hamartin and tuberin are encoded by TSC1 and TSC2 which form a GTPase activating protein heteromer that inhibits the Rheb GTPase from activating a growth promoting protein kinase called mammalian target of rapamycin (mTOR). Growths and lesions occur in the ventricular-subventricular zone (V-SVZ), cortex, olfactory tract, and olfactory bulbs (OB) in TSC. A leading hypothesis is that mutations in inhibitory neural progenitor cells cause brain growths in TSC. OB granule cells (GCs) are GABAergic inhibitory neurons that are generated through infancy by inhibitory progenitor cells along the V-SVZ. Removal of Tsc1 from mouse OB GCs creates cellular phenotypes seen in TSC lesions. However, the role of Tsc2 in OB GC maturation requires clarification. Here, it is demonstrated that conditional loss of Tsc2 alters GC development. A mosaic model of TSC was created by performing neonatal CRE recombinase electroporation into inhibitory V-SVZ progenitors yielded clusters of ectopic cytomegalic neurons with hyperactive mTORC1 in homozygous Tsc2 mutant but not heterozygous or wild type mice. Similarly, homozygous Tsc2 mutant GC morphology was altered at postnatal days 30 and 60. Tsc2 mutant GCs had hypertrophic dendritic arbors that were established by postnatal day 30. In contrast, loss of Tsc2 from mature GCs had negligible effects on mTORC1, soma size, and dendrite arborization. OB transcriptome profiling revealed a network of significantly differentially expressed genes following loss of Tsc2 during development that altered neural circuitry. These results demonstrate that Tsc2 has a critical role in regulating neural development and shapes inhibitory GC molecular and morphological characteristics.